PENGARUH DBH, DAU, DAN DAK TERHADAP TINGKAT KEMANDIRIAN PROVINSI SUMATERA SELATAN - Andrianda, Yoga; Rosada, Adelia (Universitas Sangga Buana, 2024)
Finding out how profit sharing, special allocation, and general allocation funds affect the degree of regional independence is the goal of this study. For five years, purposeful selection was done from 17 districts and cities using panel data. All of the South Sumatra Province's districts and cities that have achieved DBH, DAU, and DAK, as well as the elements that make the overall provincial monetary autonomy percentage from 2018 to 2022, make up the study sample. The General Directorate of Monetary Balance's official website provided this information. Using the SPSS version 26 software, multiple regression analysis was used to analyze the data in this study.